Implementasi Business Intelligence Untuk Menentukan Trend Penjualan Barang (Studi Kasus: PT. Menikmati Distribusi) - Ni Putu Jayanti Purwanti; I Nyoman Yudi Anggara Wijaya; Ketut Queena Fredlina (Primakara University, 2020)
This study aims to analyze the implementation of Business intelligence to determine the trend in sales of goods in response to the needs of the company, make decisions, and choosing sales strategies. Business intelligence (BI) is one of the solutions dealing with company needs, especially analyzing and providing data access to help make or take better decisions. There are several stages could help the company to facilitate the decision making process, such as database design, data warehouse design, ETL (Extract, Transform, and Load) process, OLAP cube making and followed by report making. By seeing the report analyzes, the result of this study is the sale of goods in the Makassar area has the lowest contribution compared to other areas. The lowest sales by outlet can be seen from the O Voult Legian outlet which is ranked last with the fewest sales. Therefore, based on the results above the area or outlet that has the lowest contribution must be treated specifically. Conducting promotions and discounts is one of the objectives to increase the number of orders from customers with a greater range.